2016
DOI: 10.1002/med.21391
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinones As Pharmacological Tools and Drugs

Abstract: Anthraquinones (9,10-dioxoanthracenes) constitute an important class of natural and synthetic compounds with a wide range of applications. Besides their utilization as colorants, anthraquinone derivatives have been used since centuries for medical applications, for example, as laxatives and antimicrobial and antiinflammatory agents. Current therapeutic indications include constipation, arthritis, multiple sclerosis, and cancer. Moreover, biologically active anthraquinones derived from Reactive Blue 2 have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
232
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(239 citation statements)
references
References 259 publications
(556 reference statements)
2
232
0
5
Order By: Relevance
“…Additionally, cisplatin mediates CaM crosslinking at methionine residues 43 , which could explain the decrease in FRET. We were unsurprised to observe "frequent hitters" in screens and thiol modifiers, such as Reactive Blue 44 , SCH-202676 45 , cisplatin 46 , aurintricarboxylic acid [47][48][49] , and (6 R)-BH4 50 . Several Hits that induce prominent FRET effects and/or are known functional modulators were further tested in dose-response FRET assays.…”
Section: Hts Performancementioning
confidence: 99%
“…Additionally, cisplatin mediates CaM crosslinking at methionine residues 43 , which could explain the decrease in FRET. We were unsurprised to observe "frequent hitters" in screens and thiol modifiers, such as Reactive Blue 44 , SCH-202676 45 , cisplatin 46 , aurintricarboxylic acid [47][48][49] , and (6 R)-BH4 50 . Several Hits that induce prominent FRET effects and/or are known functional modulators were further tested in dose-response FRET assays.…”
Section: Hts Performancementioning
confidence: 99%
“…Quinones are a class of organic compounds, where 9,10-anthraquinones (9,10 dioxoanthracenes) are an important subgroup [74]. Anthraquinones in Morinda citrifolia are found especially in the roots, and the main compounds with important effects on metabolism are alizarin, lucidin 3- O -β- d -primeveroside, damnacanthol-3- O -β- d -primeveroside, and rubiadin-1-methyl ether [72,73].…”
Section: Morinda Citrifolia Linn (Noni)mentioning
confidence: 99%
“…Studies have shown that AQs and their derivatives induced toxicities to the cells due to the anthracene or quinone moieties, known to be toxic to human mammary epithelial stem cells (De Flora et al, 2006;Kim, Jahan, Kabir, & Brown, 2013;Page et al, 2003). Considerable amount of information has reported that AQs and derivatives induced cytotoxicity, immunotoxicity, and carcinogenesis via alkylation or nucleophilic interaction with important cellular proteins and/or DNA (Bolton, Trush, Penning, Dryhurst, & Monks, 2000;Gorkom & Vries, 1999;Malik & Müller, 2016;Müeller et al, 1999;Müller, Eckert, Lutz, & Stopper, 1996). The studies further showed that AQs induced reactive oxygen species formation due to their highly redox active potential, leading to cellular oxidative stress.…”
Section: Toxicity Of Aqsmentioning
confidence: 99%